Clinical Outcome After Endovascular Treatment in Patients With Active Cancer and Ischemic Stroke: A MR CLEAN Registry Substudy. (8th March 2022) - Verschoof, Merelijne A.; Groot, Adrien E.; de Bruijn, Sebastiaan F.T.M.; Roozenbeek, Bob; van der Worp, H. Bart; Dippel, Diederik W.J.; Emmer, Bart J.; Roosendaal, Stefan D.; Majoie, Charles B.L.M.; Roos, Yvo B.W.E.M.; Coutinho, Jonathan M.; Dippel, Diederik W.J.; et al.
Abstract : Background and Objectives: To explore clinical and safety outcomes of patients with acute ischemic stroke (AIS) and active cancer after endovascular treatment (EVT). Methods: Using data from the Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands (MR CLEAN) Registry, we compared patients with active cancer (defined as cancer diagnosed within 12 months before stroke, metastatic disease, or current cancer treatment) to patients without cancer. Outcomes were 90-day modified Rankin Scale (mRS) score, mortality, successful reperfusion (expanded Treatment in Cerebral Infarction score ≥2b), symptomatic intracranial hemorrhage (sICH), and recurrent stroke. Subgroup analyses were performed in patients with a prestroke mRS score of 0 or 1 and according to treatment setting (curative or palliative). Analyses were adjusted for prognostic variables. Results: Of 2, 583 patients who underwent EVT, 124 (4.8%) had active cancer. They more often had prestroke disability (mRS score ≥2: 34.1% vs 16.6%). The treatment setting was palliative in 25.3% of the patients. There was a shift toward worse functional outcome at 90 days in patients with active cancer (adjusted common odds ratio [acOR] 2.2, 95% confidence interval [CI] 1.5–3.2). At 90 days, patients with active cancer were less often independent (mRS score 0–2: 22.6% vs 42.0%, adjusted OR [aOR] 0.5, 95% CI 0.3–0.8) and more often dead (52.2% vs 26.5%, aOR 3.2, 95% CI 2.1–4.9). Successful reperfusion (67.8% vs 60.5%, aOR 1.4, 95% CI 1.0–2.1) and sICH rates (6.5% vs 5.9%, aOR 1.1, 95% CI 0.5–2.3) did not differ. Recurrent stroke within 90 days was more common in patients with active cancer (4.0% vs 1.3%, aOR 3.1, 95% CI 1.2–8.1). The sensitivity analysis of patients with a prestroke mRS score of 0 or 1 showed that patients with active cancer still had a worse outcome at 90 days (acOR 1.9, 95% CI 1.2–3.0). Patients with active cancer in a palliative treatment setting regained functional independence less often compared to patients in a curative setting (18.2% vs 32.1%), and mortality was higher (81.8% vs 39.3%). Discussion: Despite similar technical success, patients with active cancer had significantly worse outcomes after EVT for AIS. Moreover, they had an increased risk of recurrent stroke. Nevertheless, about a quarter of the patients regained functional independence, and the risk of other complications, most notably sICH, was not increased. Classification of Evidence: This study provides Class I evidence that patients with active cancer undergoing EVT for AIS have worse functional outcomes at 90 days compared to those without active cancer.